Incidence of Cerebral Hemorrhage in Traumatic Patients using Computed Tomography in Tabuk City, Saudi Arabia - Ahmed, Amna Mohamed; Awad, Towmader; Yousif, Hajer; Nahari, Reem; Abdelrhman, Omnia; Elhussein, Nagwan; Zumrawi, Ebtisam; Abdalrhman, Nmariq (International Journal of Innovative Research in Medical Science, 2020)
Computed Tomography (CT) is the most commonly used imaging modality in the evaluation of cerebral hemorrhage in the head trauma patients. Objective: To study the incidence of a cerebral hemorrhage in traumatic patients using computed tomography. Method: This retrospective study was conducted at King Khalid hospital in Tabuk city, Saudi Arabia, in the radiology department, in the period from September 2018 to April 2020. The study was done by collecting 471 CT reports of patients all of them were exposed to head trauma with deferent reasons. The data were analyzed by Statistical Package for the Social Sciences (SPSS) program (ver. 20) and presented in tables and graphs according to the checklist which includes: patient age, gender, type of trauma, CT finding, and type of hemorrhage. Results: The most age group suffered from head trauma was less than 20 years percentage (55%), The male patients more exposed to head trauma than female patients with percentage (84.5%), the road traffic accident (RTA) is the most common type of trauma by percentage (63.5%), according to the CT finding; the cerebral hemorrhage represented (15.5%) with the highest percentage in a subdural hematoma (31.2%), the fracture represented (2.8%) while the normal appearance represented (81.7%) as the highest percentage. Conclusion: Most of the traumatic brain injury in patients caused cerebral hemorrhage and the CT scan reports show that: the common type of cerebral hemorrhage is subdural hematoma and it is common in males which exposed to (RTA) in the age group (21 - 40) years old.